2020
DOI: 10.1093/femsec/fiaa182
|View full text |Cite
|
Sign up to set email alerts
|

Role of amoebae for survival and recovery of ‘non-culturable’ Helicobacter pylori cells in aquatic environments

Abstract: Helicobacter pylori is a fastidious Gram-negative bacterium that infects over half of the world's population, causing chronic gastritis and is a risk factor for stomach cancer. In developing and rural regions where prevalence rate exceeds 60%, persistence and waterborne transmission are often linked to poor sanitation conditions. Here we demonstrate that H. pylori not only survives but also replicates within acidified free-living amoebal phagosomes. Bacterial counts of the clinical isolate H. pylori G27 increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Interestingly, the resuscitation of several species of VBNC bacteria upon being internalized by the amoebae has been documented by several authors (Steinert et al, 1997;Garcıá et al, 2007;Epalle et al, 2014;Casini et al, 2018;Dey et al, 2019;Dey et al, 2020) as it has been observed in this study (Table 2). To date, the mechanism of this shift is unknown and understanding the driving forces behind these interactions could allow developing more effective culture methods that might improve the detection of pathogens in their reservoirs and certain vehicles of infections.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, the resuscitation of several species of VBNC bacteria upon being internalized by the amoebae has been documented by several authors (Steinert et al, 1997;Garcıá et al, 2007;Epalle et al, 2014;Casini et al, 2018;Dey et al, 2019;Dey et al, 2020) as it has been observed in this study (Table 2). To date, the mechanism of this shift is unknown and understanding the driving forces behind these interactions could allow developing more effective culture methods that might improve the detection of pathogens in their reservoirs and certain vehicles of infections.…”
Section: Discussionsupporting
confidence: 83%
“…The resuscitation of several species of Viable But Not Culturable (VBNC) bacteria upon being internalized by the amoebae has been documented (Steinert et al, 1997;Garcıá et al, 2007;Epalle et al, 2014;Casini et al, 2018;Dey et al, 2020). The biological reason of this shift is unknown and largely unexplored.…”
Section: Analysis Of the Expression Of Rpos Genementioning
confidence: 99%
“…This study showed that H. pylori could not survive in water by itself. However, it has been suggested that H. pylori could survive inside free‐living amoebae in environmental water, such as drinking water and waste water, 29,44,45 so, it may be possible that H. pylori can survive in water through symbiosis or interaction with amoebae. The bacteria that have endured in this way may be detected as the VBNC state in drinking water, well water, and tap water.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, amoebae are also involved in VBNC resuscitation; the shift back to the culturable, active and most importantly virulent form of the bacterium. The resuscitation of several species of VBNC bacteria upon being internalized by the amoebae has been documented ( Steinert et al, 1997 ; García et al, 2007 ; Epalle et al, 2014 ; Casini et al, 2018 ; Dey et al, 2019 , 2020 ), whereby they begin multiplying within the intracellular space of the amoeba. The exact reason for this shift is unknown and relatively unexplored, however it has been reported than the presence of extracellular pyruvate and glutamate can drive the shift to the replicative form, perhaps acting as antioxidants and facilitating cell recovery ( Ducret et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…While most studies investigate the interactions of Acanthamoeba with bacteria, other free-living amoebae should also be considered. Recently, Dey and colleagues demonstrated the potential for both W. magna and Vermamoeba vermiformis to not only carry and allow multiplication of H. pylori but to resuscitate the bacteria to a culturable state ( Dey et al, 2020 ). It is becoming increasingly more evident that to minimize the risks of these pathogens to human health the whole microbial community should be considered, and further research should aim to better understand the interactions between these organisms.…”
Section: Introductionmentioning
confidence: 99%